Prevalence and factors associated with malaria in children under five years of age in Myanmar-Thailand border area. - Tin Maung Hlaing (2005)
This is a cross-sectional study to determine the prevalence of malaria among children under five years of age in Kawthaung, Myanmar-Thailand border and was conducted in June-July of 2004. This study also looked for the association between malaria infection and certain epidemiologic characteristics like distance from mosquito breding places, use of bednets, presence of cross-border traveler in the family and nutritional status of children. Anthropometry and microscopy for malaria parasite and intestinal helminth ova were done on the children. Larval survey was carried out in the sampled villages. Mothers/caretakers were interviewed for sociodemographic information. Multinomial logistic regression was utilized in model building since the outcome variable was classified into 3: 1) negative for Plasmodium falcifarum 2) Plasmodium falcifarum count less than 5,000 per microliter and 3) Plasmodium falcifarum count more than or equal to 5,000 per microliter. There were 1,047 children of 6 villages included in the study. Malaria prevalence was 22.9%. Plasmodium falcifarum constituted 95% of infections. Living far from mosquito breeding places was protective against both low density and high density malaria infection. Use of ordinary bednets also showed protective effect. The chance of having malaria infection increased in children, if there was a cross-border traveler living in their house. There was a strong association between malaria infection and stunting. Wasting was associated with low density malaria infection but not with high density malaria infection. Malaria infection was also found to associate with increase in age of the child. Use of mosquito repellents was protective against malaria infection. The chance of having malaria infection was higher in children with intestinal helminthiasis. Increase use of bednets and arrangment for proper use of insecticide treated bednets should be considered and implemented by the department concerned. Attention should be directed to the health care of cross-border travelers, particularly malaria which should be treated immediately and effectively. Programme on regular growth monitoring and nutiritonal education should be intensified. Regular deworming should be included in the local health care programme for high prevalence of intestinal helminthiasis. Composition and effectiveness of mosquito repellent should be evaluated scientifically. The community should be organized to remove or modify breeding places and render them unfavorable for mosquito breeding.